TINDAK PIDANA MANIPULASI PASAR DI PASAR MODAL INDONESIA (STUDI KASUS PUTUSAN NO. 733/PID.SUS/2019/PN.JKT.PST DAN NO. 728/PID.SUS/2019/PN.JKT.PST) - Eka Prana, Andreas; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The modus operandi in criminal activities within the Capital Market sector is quite diverse and will continue to evolve alongside the increasing use of technology. From this standpoint, law enforcement officials, particularly Prosecutors and Judges, need to continuously delve into actions suspected to fall within the formulation of market manipulation offenses under the Capital Market Law and the Capital Market Supervisory Board Law. If law enforcement officials only interpret the element of